2017
DOI: 10.1113/jp274877
|View full text |Cite
|
Sign up to set email alerts
|

N1366S mutation of human skeletal muscle sodium channel causes paramyotonia congenita

Abstract: Paramyotonia congenita is an autosomal dominant skeletal muscle channelopathy caused by missense mutations in SCN4A, the gene encoding the α subunit of the human skeletal muscle voltage-gated sodium channel NaV1.4. We report a three-generation family in which six members present clinical symptoms of paramyotonia congenita characterized by a marked worsening of myotonia by cold and by the presence of clear episodes of paralysis. We identified a novel mutation in SCN4A (Asn1366Ser, N1366S) in all patients in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 57 publications
3
14
0
Order By: Relevance
“…The mutation produces a right shift in the midpoint of the activation curve, consistent with loss of function (hypoexcitability). In contrast, N1366S (DIVS1 ENC), identified in a family diagnosed with paramyotonia congenita, produces gain of function effects including enhanced activation, slowed entry into the fastinactivated state, and accelerated recovery (Ke et al, 2017). These effects are consistent with a hyperexcitable skeletal muscle fiber phenotype that characterizes the disease.…”
Section: Functional Characterization Of Countercharge Channelopathy Mmentioning
confidence: 99%
“…The mutation produces a right shift in the midpoint of the activation curve, consistent with loss of function (hypoexcitability). In contrast, N1366S (DIVS1 ENC), identified in a family diagnosed with paramyotonia congenita, produces gain of function effects including enhanced activation, slowed entry into the fastinactivated state, and accelerated recovery (Ke et al, 2017). These effects are consistent with a hyperexcitable skeletal muscle fiber phenotype that characterizes the disease.…”
Section: Functional Characterization Of Countercharge Channelopathy Mmentioning
confidence: 99%
“…In a voltage-dependent manner, Na + channels change their conformation between permeable (open) and not permeable (e.g., closed, inactivated) states ( Hille, 2001 ), ultimately leading to the upstroke of the AP. Because of this crucial role in AP generation, genetic variants of voltage-gated Na + channels are frequently associated with pathologies of the central nervous system such as epilepsy ( Wei et al, 2017 ; Nolan and Fink, 2018 ) or pain syndromes ( Rühlmann et al, 2020 ), of skeletal muscle such as paramyotonia ( Ke et al, 2017 ), and of the heart, where they can cause arrhythmias ( Lieve and Wilde, 2015 ; Veerman et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Of note, structural studies showed that N1366 in DIVS1 forms hydrogen bonds with R1457 (R4) in DIVS4, and a functional study of N1366D (replaced with a negatively charged residue) displayed a hyperpolarizing shift in steady-state availability, altered voltage-dependence of fast inactivation and delayed recovery from inactivation, causing a loss-offunction of Na v 1.4 [9,15] (Table 2). Conversely, N1366S (replaced with an uncharged residue), found in PC, displayed a cold-induced hyperpolarizing shift in activation, depolarizing shift in steady-state availability, delayed fast inactivation and accelerated recovery from inactivation, causing a gain-of-function of Na v 1.4 that can be associated with PC [54] (Table 2). Intriguingly, a structural study of N1366S demonstrated disrupted interactions of N1366S and an arginine residue in DIVS4 at low temperature [54].…”
Section: Defective Inactivation By Mutations Of Pgctc In Na V 14 Divmentioning
confidence: 99%
“…Conversely, N1366S (replaced with an uncharged residue), found in PC, displayed a cold-induced hyperpolarizing shift in activation, depolarizing shift in steady-state availability, delayed fast inactivation and accelerated recovery from inactivation, causing a gain-of-function of Na v 1.4 that can be associated with PC [54] (Table 2). Intriguingly, a structural study of N1366S demonstrated disrupted interactions of N1366S and an arginine residue in DIVS4 at low temperature [54]. On the other hand, a structural study showed that D1420, one of the residues of pGCTC, in Na v 1.4 DIVS3 is in close proximity to R1635 (R5) in DIVS4, and a functional study showed that D1420K (replaced with a positively charged residue) displayed a delayed fast inactivation and altered voltage-dependence of recovery from inactivation (Table 2) [15].…”
Section: Defective Inactivation By Mutations Of Pgctc In Na V 14 Divmentioning
confidence: 99%